2015
DOI: 10.1002/cne.23792
|View full text |Cite
|
Sign up to set email alerts
|

Corticalization of motor control in humans is a consequence of brain scaling in primate evolution

Abstract: Control over spinal and brainstem somatomotor neurons is exerted by two sets of descending fibers, corticospinal/pyramidal and extrapyramidal. Although in nonhuman primates the effect of bilateral pyramidal lesions is mostly limited to an impairment of the independent use of digits in skilled manual actions, similar injuries in humans result in the locked-in syndrome, a state of mutism and quadriplegia in which communication can be established only by residual vertical eye movements. This behavioral contrast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The human CNS is possibly the most complex biological tissue, comprising on average 86.1 billion neurons in the brain and spinal cord in males, along with a roughly equal number of glial cells (Herculano-Houzel, 2009; Herculano-Houzel et al, 2015). The neocortex alone contains approximately 16.34 billion neurons (Herculano-Houzel, 2009) and 164 trillion synapses, points of communication between neurons (Tang et al, 2001).…”
Section: A Brief Overview Of Human Cns Cellular Organization and Compmentioning
confidence: 99%
See 1 more Smart Citation
“…The human CNS is possibly the most complex biological tissue, comprising on average 86.1 billion neurons in the brain and spinal cord in males, along with a roughly equal number of glial cells (Herculano-Houzel, 2009; Herculano-Houzel et al, 2015). The neocortex alone contains approximately 16.34 billion neurons (Herculano-Houzel, 2009) and 164 trillion synapses, points of communication between neurons (Tang et al, 2001).…”
Section: A Brief Overview Of Human Cns Cellular Organization and Compmentioning
confidence: 99%
“…The human CNS contains approximately 86.1 billion neurons on average in 50 to 70 year-old males (Azevedo et al, 2009; Herculano-Houzel, 2015). There are approximately 16.34 billion neurons in the cerebral neocortex (Azevedo et al, 2009; Herculano-Houzel, 2009) and approximately 700 million additional neurons in the cerebral white matter when analyzed in young children (Sigaard et al, 2014).…”
Section: A Brief Overview Of Human Cns Cellular Organization and Compmentioning
confidence: 99%
“…In addition to structurally based studies, a recent comparative functional magnetic resonance imaging study observed two lateralized human fronto-parietal networks in the cortical regions displaying the greatest evolutionary expansion that had neither topological nor functional monkey correspondents (Mantini et al, 2013), suggesting that functions of certain structural networks have diverged during human evolution. There is also evidence for structural and functional reorganization of corticofugal neurons and their long-range axons, such as the corticospinal projection system in primates (Heffner and Masterton, 1983; Herculano-Houzel et al, 2016; Kuypers, 1987; Nakajima et al, 2000), which might be relevant for the corticalization of motor control and the evolution of digital dexterity.…”
Section: Evolutionary Perspective On Human Nervous System Structurementioning
confidence: 99%
“…This increase in size relative to other thalamic structures [64] may result in the pulvinar contributing to a wider range of cognitive abilities than in other primates. In that sense, simple scaling rules may change the balance in a way that results in larger-brained primates having increased corticospinal control over their movements [69]. …”
Section: Human Pulvinar Characteristicsmentioning
confidence: 99%